PERLINDUNGAN HUKUM ATAS KARYA CIPTA FOTOGRAFI YANG DIPUBLIKASIKAN TANPA IZIN DITINJAU DARI UNDANG-UNDANG HAK CIPTA YANG TERJADI DI KABUPATEN SANGGAU - NIM. A1012161166, VANCA VERLANDA (Fakultas Hukum Universitas Tanjungpura, 2022)
Abstrac Photographic copyrights are one of the protected works under Article 40 letter k of Law Number 28 of 2014 concerning Copyrights because photographic copyrights are the result of creative activities, a thinking ability or human brain processing which is then expressed in the form of photos that have benefits. and has economic value. If someone uses a photograph for a particular interest without first asking permission from the creator, then it violates the Copyright Law, as stated in Article 2 paragraph (1) of the Copyright Law. An example of this is when MSZ, a photographer in Sanggau City, did a photo shoot for the bride and groom who were getting married. Photos of the bride and groom will be used for advertisements or promotions that the photographer has created. However, the wedding photos were later published by VE, another photographer, without MSZ's approval and permission. Based on the case above, it is clear that MSZ does not get legal protection for the photographic works it creates, even though photographic works are one of the copyrights.The formulation of the problem in this study is: